Building for God and Mammon: The Combination of Religious and Commercial Spaces in Chicago’s “Methodist Church Block” - Munteán, László (FOCUS: Papers in English Literary and Cultural Studies, 2006)
In the midst of the bustle of downtown Chicago stands a skyscraper of quite peculiar shape. What seems to be an office tower with identical window surfaces up to the 21st floor abruptly turns into a Gothic church steeple with a cross on its top. Puzzled and confused at the sight of such a combination of emblematic architectural codes the outsider cannot help but ponder: ‘What’s going on here?’ Although dwarfed by the soaring heights of newer high-rises, the building’s location at the comer of Washington and Clark Streets, facing the public square in front of the Daley Center still offers fairly good visibility of its entire Washington Street facade.